2013
DOI: 10.1097/pgp.0b013e31826f5cf6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Expression of Cyclin D1, p16Ink4a, p21WAF1, and Ki-67 Correlates With the Severity of Cervical Neoplasia

Abstract: High-risk human papillomaviruses are closely associated with cervical cancer and its precursor lesions through interactions between the E6 and E7 oncoproteins and the cell-cycle regulatory proteins, such as p53 and pRb, respectively. As other molecules involved in the cell-cycle control seem to be important for human papillomavirus (HPV)-mediated cervical carcinogenesis, we have analyzed the expression of p53, p21, p16, cyclin D1, and Ki-67 and the presence of HPV (HPV pool and HPV-16) by immunohistochemical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
4
21
0
Order By: Relevance
“…CDKN1A was found to be hypermethylated in less than 10% of cervical cancer samples [31]. This is consistent with the reports of high levels of p21 in cervical cancer samples, which was also shown to be associated with the progression of lesions in several studies [23,24,86,87].…”
Section: Cell Cycle Regulation and Dna Repairsupporting
confidence: 86%
“…CDKN1A was found to be hypermethylated in less than 10% of cervical cancer samples [31]. This is consistent with the reports of high levels of p21 in cervical cancer samples, which was also shown to be associated with the progression of lesions in several studies [23,24,86,87].…”
Section: Cell Cycle Regulation and Dna Repairsupporting
confidence: 86%
“…It has been shown that cell cycle proteins p16, Ki‐67, cyclin D1, p53 and ProEx C are altered in 144 cervical tissue samples, showing increased proliferation . Molecules related to cell proliferation have a significant increase from low‐grade to high‐grade lesions and cancer in HPV‐associated cancers .…”
Section: The Consequences Of Signaling Alterations In Human Papillomamentioning
confidence: 99%
“…In a nested study by Carozzi and colleagues, it was shown that p16 overexpression is a marker for CIN2 or worse or for its development within 3 years in HPV-positive women 123. Ki-67 and p16 are complimentary alternative biomarkers for HPV-related neoplasia 124,125. Cytokeratin (CK) 17 is a useful marker for endocervical reserve stem cells, which gives rise to metaplasia and antibody to CK17 is used to differentiate between immature squamous metaplasia and high-grade CIN (CIN III) 126.…”
Section: Biomarkers Used In Hiv-associated Cervical Cancer Diagnosis/mentioning
confidence: 99%